EMBRYO IMPLANTATION FAILURE - Kamalov Mukhammadali Iskanderovich; Yerubay Aidana Suyunshibaykyzy; Shonykbaeva Saltanat Sapargalievna (Progress in Science, 2024)
Implantation is the first stage of cross-interaction between the embryo and the endometrium, which is a key point for a successful pregnancy. The implantation process involves apposition, adhesion, and invasion. Successful implantation is defined as an intrauterine gestational sac visible on ultrasound. Failure of implantation can occur during the process of attachment and migration, with a negative urine or blood test for human chorionic gonadotropin (hCG), or if the intrauterine gestational sac does not form with a positive hCG. Recurrent implantation failure (RIF) is a clinical phenomenon that does not have a generally accepted definition. Key factors to consider when determining RIF are the number of embryos transferred or failed IVF cycles, the quality of the embryos, whether the embryos are fresh or frozen, and the age of the mother, which is controversial. The increase in the cumulative live birth rate with increasing number of IVF-ET cycles showed a gradual decrease (1). Other analyzes have shown that after three cycles of IVF-ET, the cumulative pregnancy rate does not increase significantly, and the pregnancy rate per cycle tends to decrease after three failed treatment cycles (2–4). When RIF was defined as two or more implantation failures, the live birth rate was significantly lower than when RIF was defined as three or more implantation failures, which was considered to be an overinflated denominator (5). Therefore, blindly increasing the number of IVF-ET cycles may not lead to successful pregnancy, and we need to establish a cut-off point for treatment cycles to recognize patients with RIF. Due to varying embryo quality, the number of embryos transferred varies from 3 to 10 or more (6). A good quality embryo has an appropriate developmental status depending on the day of its development (7). A low-quality embryo means that in order for a successful pregnancy to occur, the patient needs to transfer a larger number of embryos. Another factor to consider when determining RIF is the age of the mother. It is well known that pregnancy rates decrease with maternal age (8); older patients require more blastocyst transfer cycles to achieve the same implantation rate as younger women (9). Determining RIF without taking into account the mother's age does not make sense. Based on the above considerations, the generally accepted definition of FIF, as presented by Coughlan, is the failure to achieve a clinical pregnancy after the transfer of at least four good quality embryos over a minimum of three fresh or frozen cycles in a woman under 40 years of age (10). The European Society of Human Reproduction and Embryology (ESHRE) Preimplantation Genetic Diagnosis Consortium has defined RIF as when more than three transfers of good quality embryos or ten embryos in multiple transfer cycles do not result in a clinical pregnancy (11). In clinical practice, an international survey of clinicians and embryologists found that the majority defined RIF as failure of embryo transfer in three cycles, either fresh or frozen, with no agreement on the upper cut-off age (6).